Підсумки інтродукції та селекції тифону (Brassica rapa L. × B. campestris f. biennis DC.) у Національному ботанічному саду ім. М.М. Гришка НАН України - Rakhmetov, D.B.; Rakhmetova, S.О. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
The aim – to summarize of results on introduction and breeding of Tyfon (Brassica rapa L. × B. campestris f. biennis DC.) in M.M. Gryshko National Botanical Garden of the NAS of Ukraine and to establish biological, morphological characteristics, productive and energy potential of different forms and varieties. Material and Methods. Field, introduction, bio-morphology and breeding methods were used. Chemical analyses were performed in the biochemical laboratory of department of new crops of M.M. Gryshko National Botanical Garden of the NAS of Ukraine. Lipid content was estimated using the Soxtherm extraction system. The energy value of samples was calculated with the C200 calorimeter system. Results. Long-term consequences of introduction and breeding of Tyfon are presented. Valuable gene pool of Tyfon plants is collected. Highly adaptive forms and varieties are bred, of which 3 are included in the State Register of plants varieties of Ukraine. The biological, morphological, ecological, and allelopathic characteristics of plants are established. The biochemical composition of plant phytomass and seeds depending on morphological features, vegetation conditions and specific cultivation conditions is defined. Harvesting and productive potential of tyfon is determined, possible feed, technical, energy, and nutritional applications are presented. Fatty acid composition of oil is evaluated. Energy values of the main product (oil) and byproducts (feed, straw) for biofuel production are given. Conclusions. High yield of phytomass (81.6–93.5 t/ha), seeds (4.4–4.5 t/ha), and oil content (1.73–1.86 t/ha) for highly adaptive plants (Phytopal, Obriy) are established. They provide a large output per unit area in absolute dry matter (phytomass – 23.0–25.2 t/ha, seeds – 4.0–4.1 t/ha), characterized by high heat capacity of raw material (phytomass – 4121–4490 kcal/kg, seeds – 6221–6273 kcal/kg, oil – 9450–9447 kcal/kg) and high energy output (phytomass – 94.8–113.2 Gcal/ha, seeds – 27.8–28.0 Gcal/ha, oil – 18.0–19.2 Gcal/ha).